Tracking Financial Flows after Disasters : Reconstruction Expenditure Tracking Analysis Methodology (RETAM) - Fengler, Wolfgang (World Bank, Washington, DC, 2012)
This note presents a financial tracking methodology developed by the World Bank's Indonesia country team. Following the tsunami and the subsequent earthquakes in Nias (2005) and Yogyakarta (2006), the team has produced several reconstruction finance updates and monitored the sources and uses of the funding. The methodology is a relatively simple accounting tool centered on the generation of a core table to facilitate sectoral and geographical analysis and is based on three methodological principles: (i) the comprehensiveness of expenditures; (ii) a specific focus on reconstruction expenditures; and (iii) matching the sectoral classifications in the Damage and Loss Assessment.